(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The primary focus of this paper is on how analogy functions rhetorically in the post-Romantic discourse on the death of the author, and where this rhetoric begins to break down. In this paper I will examine three rhetorical tropes employed by Eliot, Jung, and Barthes who resort to analogies in order to advance their arguments in such a seductive way that a counter-argument seems an exercise in futility at best and an unthinkable task at worst. I regard these theorists as rhetoricians because their basic approach, despite their scientific posturing, is to persuade their audience by rhetorical rather than empricial means. However, we may do well to approach their arguments with the skeptic notion that the use of most, not to say all, rhetorical strategies occurs at a critical juncture in the discursive formation, and thus is essentially a means of overcoming an argumentative hurdle. The crucial issue raised by this paper is: If the method is questionable, then won’t the conclusions reached with the help of that method be questionable as well? الهدف الأساسي لهذا البحث هو تسليط الضوء على الوظيفة البلاغية لمنطق القياس (التشبيه) الذي لجأ إليه إليوت ويونغ وبارت ليعلنوا موت المؤلف. ويدرس البحث الحِيَل البلاغية التي استخدمها هؤلاء في حِجاجهم في هذه المسألة. وينظر البحث إلى هؤلاء البلاغيين بصفة كونهم بلاغيين لا نقاداً، لأن تناولهم لهذه المسألة، رغم تظاهرهم بالاتكاء على المنهج العلمي، يهدف أساساً إلى الحِجاج من طريق البلاغة (الفهلوية) لا من طرقٍ علمية قابلة للاختبار. وهذا أوجب على البحث أن يتناول محاججاتهم بشيءٍ من التشكيك، إذ إن معظم، إن لم نقُل كل، الاستراتيجيات البلاغية يلجأ إليها من يلجأ عندما تصل محاججته إلى طريق مسدودة. وعليه، فهي من حيث الجوهر وسيلة لتخطي هذا المأزق. المسألة التي يثيرها هذا البحث هي: إذا كان المنهج الذي استخدمه هؤلاء البلاغيون مشكوكاً في صحته، ألا يحق لنا أن نشكك في صحة استنتاجاتهم أيضاً؟